Revisiting long-term prognostic factors of biliary atresia: A 20-year experience with 81 patients from a single center - Damla Hanalioğlu,; Hasan Özen,; Asuman Karhan,; Ersin Gümüş,; Hülya Demir,; İnci N. Saltık-Temizel,; Saniye Ekinci,; İbrahim Karnak,; Arbay O. Çiftçi,; Feridun C. Tanyel,; Aysel Yüce, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The present study aimed at investigating the long-term outcomes and prognostic factors of patients with biliary atresia (BA) diagnosed and followed at a single center. Materials and Methods: Patients with BA treated during 1994-2014 at a large-volume pediatric tertiary referral center were reviewed retrospectively with regard to demographic, clinical, laboratory, and diagnostic characteristics for identifying the prognostic factors and long-term clinical outcomes. Results: Overall, 81 patients (49 males, 32 females) were included. Mean age at diagnosis was 73.1±4.7 (median: 64) days. Of the patients included, 78 patients (96%) underwent a portoenterostomy procedure. Mean age at operation was 76.8±4.7 (median: 72) days. The surgical success rate was 64.8%. A younger age (either at diagnosis or surgery) was the only determinant of surgical success. The 2-, 5-, and 10-year overall survival (OS) rates, including all patients with or without liver transplantation, were 75%, 73%, and 71% respectively, whereas the 2-, 5-, and 10-year survival rates with native liver (SNL) were 69%, 61%, and 57%, respectively. Mean follow-up duration was 9.4±7.5 years. Successful surgery, presence of fibrosis and/or cirrhosis on the liver pathology, and prothrombin time [international normalized ratio (INR)] at presentation were independent prognostic factors for both OS and SNL. Conclusion: A younger age at diagnosis is strongly associated with surgical success in BA. Surgical success, the prothrombin time (INR) at presentation, and liver pathology are independent prognostic factors affecting the long-term outcomes in patients with BA. Therefore, timely diagnosis and early referral to experienced surgical centers are crucial for optimal management and favorable long-term results in BA. Cite this article as: Hanalioğlu D, Özen H, Karhan A, et al. Revisiting long-term prognostic factors of biliary atresia: A 20-year experience with 81 patients from a single center. Turk J Gastroenterol 2019; 30(5): 467-74.